Optical fibre Bragg grating recorded in TOPAS cyclic olefin copolymer - Bang, Ole; Johnson, Ian P.; Yuan, Wu; Stefani, Alessio; Nielsen, Kristian Fog; Rasmussen, Henrik Koblitz; Khan, Lutful; Webb, David J.; Kalli, Kyriacos (My University, 2011)
A report is presented on the inscription of a fibre Bragg grating into a microstructured polymer optical fibre fabricated from TOPAS cyclic olefin copolymer. This material offers two important advantages over poly (methyl methacrylate), which up to now has formed the basis for polymer fibre Bragg gratings: TOPAS has a much lower water affinity and has useful properties for biosensing. The grating had a Bragg wavelength of 1569nm and a temperature sensitivity of -36.50.3 pm/C.
Keywords: Plastic Optical Fiber; Bragg Grating; Inscription